Pengembangan Video Pembelajaran Powtoon Dalam Model Discovery Learning Untuk Meningkatkan Pengetahuan Pada Siswa Kelas Viii Smpn 2 Kademangan - Nur Isroatul Khusna; Arif Rahman Alwan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research is motivated by students' lack of interest in educational media during learning. Students feel bored and less motivated because the media used is only conventional, such as lecturing, relying on textbooks and modules, which result in low student knowledge. Powtoon learning videos, with their modern approach and visual-audio presentation, offer a solution. These videos feature animated cartoons, which address students' complaints about conventional learning methods. This research aims to understand the overview of the learning process, identify student needs, determine the steps for media development, assess the validity of the developed media, and examine the influence of the media on students' knowledge. The researcher employed the Research and Development (R&D) approach using the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques included questionnaires, tests, interviews, observations, and data analysis. The study was conducted at SMPN 2 Kademangan, with eighth-grade classes D (control group) and E (experimental group) as research subjects. Data analysis was performed using quantitative and qualitative methods. The validation results from media experts, subject matter experts, and social studies teachers regarding the Powtoon media showed that it was suitable for use with minor revisions and had a significant impact on learning outcomes. The Sig value (2-tailed) was found to be 0.003, which is less than the significance level of 0.05. Therefore, H1 is accepted, indicating that there is a difference in learning outcomes between the control group (class D) and the experimental group (class E), with an average post-test score of 82.68% for class D and 93.28% for class E. This shows a difference of 10.6%, indicating that Powtoon media is effective for learning purposes.